Development strategies for creative small and medium enterprises (SMEs): A Quintuple Helix Model approach to support smart city initiatives - Dahmiri Dahmiri; Idham Khalik; Rizky Azika Ramadhan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study explores the development of Creative Small and Medium-Sized Enterprises (SMEs) in the food, textile, and handicraft sectors in Jambi City, employing the quintuple helix model to align with the Smart City concept. The research gathered primary data through surveys, interviews, and focused group discussions (FGDs). The study encompassed a diverse range of stakeholders from the specified sectors, with a sample size of 100 individuals. A mixed-method research approach was adopted, integrating both qualitative and quantitative methods. Analytical tools such as the Likert scale, SWOT analysis, and the quintuple helix model were employed for data analysis and interpretation. The findings reveal that many participants in these sectors were women, predominantly with high school-level education. The age group of 46-55 years was most represented among the respondents. Notably, the food sector emerged as the dominant industry among the studied SMEs, attributed to its relative ease of establishment and cost-effectiveness compared to the textile and handicraft sectors. The study also examined the perceptions of the roles of quintuple helix actors (government, academia, industry, society, and social environment) in the development of these SMEs. The findings indicate a generally positive perception, suggesting effective fulfillment of roles by these actors. This collaborative effort within the quintuple helix framework has positively impacted the development of creative SMEs in Jambi City, contributing significantly to the Smart City initiative. The study underscores the importance of such collaboration in fostering the growth and sustainability of creative SMEs in the context of urban development.